2020
DOI: 10.1089/cbr.2019.3046
|View full text |Cite
|
Sign up to set email alerts
|

MiR-524-5p Suppresses Migration, Invasion, and EMT Progression in Breast Cancer Cells Through TargetingFSTL1

Abstract: Background: The effects of miR-524-5p on breast cancer (BC) have not been investigated, though studies show that miR-524-5p has an anticancer function. Thus, this study investigated the effects of miR-524-5p on BC cells and its potential molecular mechanism. Materials and Methods: The expression of miR-524-5p from the collected BC samples was determined. Cell counting kit-8 (CCK-8) assay was performed to examine the effect of miR-524-5p on BC cells viability. The target for miR-524-5p was predicted by bioinfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…microRNAs are also crucial players involved in tumorigenesis 23 . For example, both miR‐197‐3p and miR‐451a are down‐regulated in PCa, and they inhibit the proliferation and invasion of PCa cells, and promote their apoptosis 24,25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…microRNAs are also crucial players involved in tumorigenesis 23 . For example, both miR‐197‐3p and miR‐451a are down‐regulated in PCa, and they inhibit the proliferation and invasion of PCa cells, and promote their apoptosis 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…microRNAs are also crucial players involved in tumorigenesis. 23 For example, both miR-197-3p and miR-451a are down-regulated in PCa, and they inhibit the proliferation and invasion of PCa cells, and promote their apoptosis. 24,25 miR-384 is a tumor suppressor, which is down-regulated in osteosarcoma and papillary thyroid cancer, and inhibits tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Among miR-200c predicted targets, we found FSTL1. Since it has been recently documented the importance of epicardial FSTL1 in cardiac regeneration [ 21 ] and its involvement in airway and cancer EMT [ 28 , 29 ], we hypothesized that (1) FSTL1 could be also involved in epicardial EMT (2) through a miR-200c-dependent pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Further, previous results already demonstrated that FSTL1 induced EMT in the airways of patients and mice by activating autophagy, and miR-524-5p/FSTL1 has the ability of regulating the progression of EMT of breast cancer cells [ 28 , 29 ]. Similarly, in our study, using an in vivo model of myocardial infarction in mice, we detected a strong upregulation of FSTL1 in epicardial cells undergoing EMT during acute MI.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that LINC00313 upregulates the expression of the pro-apoptotic proteins Bax and caspase-3/9 and inhibits the expression of the anti-apoptotic protein Bcl-2. E-cadherin, N-cadherin, Vimentin, and MMP-2 are markers of cell migration and invasion [29]. N-cadherin, Vimentin, and MMP-2 expression was signi cantly inhibited in response to the overexpression of LINC00313 in cells, and E-cadherin expression was signi cantly increased in response to LINC00313 overexpression.…”
Section: Discussionmentioning
confidence: 99%